2020
DOI: 10.1002/14651858.cd001862.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for preventing ophthalmia neonatorum

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 139 publications
1
13
0
Order By: Relevance
“…Of 24 infants that received tetracycline prophylaxis, 11 tested positive for chlamydial ophthalmia neonatorum, including both confirmed and probable cases of infection. The cases reported in our study reinforce that tetracycline prophylaxis is not effective at preventing chlamydial ophthalmia neonatorum, and helps clarify findings from a recent Cochrane review 44 which had suggested, with low certainty, some efficacy for tetracycline. All but one infant had received the standard ocular tetracycline prophylaxis at birth.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Of 24 infants that received tetracycline prophylaxis, 11 tested positive for chlamydial ophthalmia neonatorum, including both confirmed and probable cases of infection. The cases reported in our study reinforce that tetracycline prophylaxis is not effective at preventing chlamydial ophthalmia neonatorum, and helps clarify findings from a recent Cochrane review 44 which had suggested, with low certainty, some efficacy for tetracycline. All but one infant had received the standard ocular tetracycline prophylaxis at birth.…”
Section: Discussionsupporting
confidence: 77%
“…39 However, while those agents have been shown to be effective for preventing ophthalmia neonatorum from N. gonorrhoeae, there is no antimicrobial agent that has been shown to reliably prevent ophthalmia neonatorum resulting from C. trachomatis. 12,43 In a recently published Cochrane review to determine optimal prophylactic regimens, 44 the authors summarized evidence from 30 trials, only 4 of which were carried out in African countries (Angola, Kenya, and Zaire). Using blindness (or other adverse visual outcomes) or conjunctivitis at 1 month, the authors reported that compared to no prophylaxis, any of tetracycline, erythromycin, povidone iodine, or silver nitrate had very limited effect (0.96, 95% CI 0.57-1.61) on the risk of chlamydial ophthalmia neonatorum.…”
Section: Preventionmentioning
confidence: 99%
See 2 more Smart Citations
“…The infection, usually contracted from the mother’s infected birth canal during vaginal delivery, can cause corneal damage and vision loss. In the past, the term mainly defined conjunctival infections caused by Chlamydia trachomatis and Neisseria gonorrhea , which are the pathogens most frequently responsible for permanent ocular damage [ 1 , 2 ]; currently, ON also defines neonatal conjunctivitis caused by other bacteria [ 3 ]. The incidence of ON by N. gonorrhoeae has significantly decreased with the widespread use of conjunctival antibacterial prophylaxis with 2% silver nitrate, introduced by Karl Franz Credè in Germany at the end of the 19th century [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%